2015
DOI: 10.1017/s0068245414000227
|View full text |Cite
|
Sign up to set email alerts
|

The Christianisation of the Peloponnese: The Case for Strategic Change

Abstract: The issue of the persistence of paganism is now quite well considered; however, it is only in recent times that the same concern approached from another perspective, the multifaceted nature of the Christianisation of the Peloponnese, has become the topic of detailed discussion. It is likely that Christianisation in Achaea took place incrementally and with a variety of effects according to the location. The processes of how this took place and under what circumstances remain to be discussed in detail. As a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 82 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…One of the inferred earthquakes seems to have facilitated (or even triggered) the transition from the Roman, pagan culture to the Christian culture (excavation #40), in analogy to Crete (Stiros & Papageorgiou, ). Apart from this example, no historical or cultural gaps followed these inferred earthquakes (Sweetman, ), but life seems to have continued though at a much lower level, at least in some cases, and may have probably caused a gradual decline of the town since the 4th c . AD.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…One of the inferred earthquakes seems to have facilitated (or even triggered) the transition from the Roman, pagan culture to the Christian culture (excavation #40), in analogy to Crete (Stiros & Papageorgiou, ). Apart from this example, no historical or cultural gaps followed these inferred earthquakes (Sweetman, ), but life seems to have continued though at a much lower level, at least in some cases, and may have probably caused a gradual decline of the town since the 4th c . AD.…”
Section: Discussionmentioning
confidence: 93%
“…One of the inferred earthquakes seems to have facilitated (or even triggered) the transition from the Roman, pagan culture to the Christian culture (excavation #40), in analogy to Crete (Stiros & Papageorgiou, 2001). Apart from this example, no historical or cultural gaps followed these inferred earthquakes (Sweetman, 2015), but life seems to have continued though at a much lower level, at least in some cases, and may have probably caused a gradual decline of the town since the 4th c. AD. The legend for the transportation of the remains of St. Andrewswho was martyred in Patras on an X-type cross-to Scotland (Stiros & Pytharouli, 2014) in the sixth century may also be related to the decline of Patras after a destructive earthquake, but this is only a hypothesis.…”
Section: Earthquakes and Historical Reportsmentioning
confidence: 88%
See 1 more Smart Citation
“…A topographic analysis of the Late Antique churches of the Peloponnese showed that the process of Christianisation of the region was a result of strategic change with planned and unintended outcomes (Sweetman 2015b). Given the persistent issues concerning secure chronologies for church foundations, this study approached questions of Christianisation through an innovative methodology: locations of churches were used as indices of change; their construction was attributed – depending on their topographic location – to a range of sociological processes, such as complexity, social movement and tipping point (Sweetman 2015b). Churches built in large port towns in the north-east (such as Kiato), and on the edges of major sanctuaries (like Epidavros), are likely to have been strategic foundations with intended outcomes.…”
Section: Introduction: History and Topography Of The Late Antique Pelmentioning
confidence: 99%
“…Through more organic processes of unplanned change, articulated through social movement (which includes patronage, inheritance and other factors), it is likely that church building in the Peloponnese spread from sanctuaries and ports through a range of network connections (including, but not limited to, clerical, local and governmental factors) to the edges of busy towns such as Corinth and Argos (Sweetman 2015a). Within the broader context of the urban sphere, it is likely that the earliest churches were located on the edges of the Roman town and often on major routes, or in cemeteries, making the best of existing gathering-points (Sweetman 2015b). Churches erected in the centre of urban space, sometimes reusing earlier buildings, often represent a later phase of urban construction which commenced only after a number of Christian churches had already been well established in the surrounding area.…”
Section: Introduction: History and Topography Of The Late Antique Pelmentioning
confidence: 99%